Implementing Food Safety to Produce Good Food Quality during the Covid-19 Pandemic at Taco Casa Canggu - I Nyoman Cahyadi Wijaya; Ni Ketut Dewi Irwanti; Komang Astiari (Catuspata Press, 2022)
Purpose: This study aims to analyze the implementation of food safety on producing good food quality at Taco Casa Canggu in Bali, Indonesia, and what efforts are being made to ensure food safety in preparing good food quality in the era of the Covid-19 pandemic. Research methods: A qualitative descriptive method is used to analyze the implementation specifically. Primary data were collected through interviews and observation. The research instruments used were an interview guideline and an observation checklist. Findings: The restaurant management had rearranged the standard operating procedure on food safety according to the Indonesian Minister of Health and the World Health Organization, transforming business from offline to online (O2O) by enhancing home delivery service and digitalizing their service and marketing. Implication: The restaurant management has added strict standard operational procedures on some aspects, such as performing body temperature checks for third parties and costumers and creating a planning meal timeline according to day-by-day service.